2020
DOI: 10.1002/capr.12363
|View full text |Cite
|
Sign up to set email alerts
|

Online counselling and goal achievement: Exploring meaningful change and the types of goals progressed by young people

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 63 publications
1
27
1
Order By: Relevance
“…This was followed by goals concerning personal growth, although the third most common type of goals set focussed on managing interpersonal difficulties. This reflects previously cited research which reported that children and young people set goals related to personal growth and independence, functioning, coping with specific symptoms and problems, understanding and improving self‐expressing emotions and relationship/interpersonal difficulties (Bradley et al., 2013; Jacob et al., 2016, 2020). The fact that young adults were more likely to set personal growth goals and adolescents focussed on developing coping mechanisms may be reflective of developmental stage (Scales et al., 2016).…”
Section: Discussionsupporting
confidence: 82%
“…This was followed by goals concerning personal growth, although the third most common type of goals set focussed on managing interpersonal difficulties. This reflects previously cited research which reported that children and young people set goals related to personal growth and independence, functioning, coping with specific symptoms and problems, understanding and improving self‐expressing emotions and relationship/interpersonal difficulties (Bradley et al., 2013; Jacob et al., 2016, 2020). The fact that young adults were more likely to set personal growth goals and adolescents focussed on developing coping mechanisms may be reflective of developmental stage (Scales et al., 2016).…”
Section: Discussionsupporting
confidence: 82%
“…Initially, four domains of wants and needs were identified from Kooth's Theory of Change that represent the needs for mental health support in children and young people that access the web-based therapy service (Hanley et al, 2020;Hanley et al, 2021). Such domains were also previously explored investigating the goals collaboratively set by young people at the onset of their contact with the service (Hanley et al, 2017;Jacob et al, 2020). These domains allowed to set the parameters of the constructs that the measure will be seeking to capture concerning what children and young people seek in an online service, for example, whether individuals seek informational or emotional support and whether this support was directed to support interpersonal or intrapersonal change.…”
Section: Phase I: Item Generationmentioning
confidence: 99%
“…Where the articulated goals moved, it was notable that students reported high levels of goal achievement and that these goals moved further than in comparable data with young populations ( Jacob et al, 2021 ). As with earlier studies in web-based therapeutic resources ( Musiat et al, 2014 ; Santucci et al, 2014 ), despite aiming to be student focused, the service had a relatively high attrition rate.…”
Section: Discussionmentioning
confidence: 84%
“…Kooth Student proves no exception and, as a consequence, a number of the individuals who articulated goals would not have returned to them to report progress. In accounting for this, some studies only consider those individuals’ who return to the goals that they articulate ( Jacob et al, 2021 ), whereas the data reported here included goal scores that both were and were not returned to. Given the varied ways that individuals use web-based services, the importance of developing appropriate means of successfully monitoring such work proves vitally important for service providers such as this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation